Multivariate prognostic models for patients with stages I and II colon carcinoma: a strobe-compliant retrospective cohort study - Luis F. Oñate-Ocaña; Roberto Herrera-Goepfert; Alejandro Avilés-Salas; Carlo C. Cortés; Sagrario González-Trejo; José F. Carrillo; Erika Ruiz-García; Francisco J. Ochoa-Carrillo; Vincenzo Aiello-Crocifoglio; Claudia M. García-Cuellar (Revista de Investigación Clínica, 2023)
Background: Colorectal cancer is the most frequent gastrointestinal malignancy worldwide. The value of adjuvant treatment is controversial in Stages I and II. Objective: The aim of this study was to construct post-operative prognostic models applicable to patients with stages I-II colon carcinoma (CC). Methods: This is a retrospective cohort study of patients with Stage I-II CC treated over a 25-year period. Exposure was defined as clinical, histopathological, and immunohistochemical factors (including CDX2 and MUC2 expression). Patients were randomly allocated to either a “modeling set” or a “validation set”. Factors associated with recurrence, disease-free survival (DFS), and overall survival (OS) were defined in the “modeling set”. Their performances were tested in the “validation set”. Results: From a total of 556 recruited patients, 339 (61%) were allocated to the “modeling set” and 217 (39%) to the “validation set”. Three models explaining recurrence, DFS, and OS were described. Tumor location in the left colon (Hazards ratio [HR] = 1.57; 95% Confidence interval [CI] 0.99-2.48), lymphocyte (HR = 0.46; 96% CI 0.27-0.88) and monocyte (HR = 0.99; 95% CI 0.99-1) counts, neutrophil/platelet ratio (HR = 1.3; 95% CI 0.74-2.3, and HR = 2.3; 95% CI 1.3-4.1; for second and third category, respectively), albumin/monocyte ratio (HR = 0.43; 95% CI 0.21-0.87), and microscopic residual disease after surgery (HR = 8.7; 95% CI 3.1-24) were independently associated with OS. T classification and expression of CDX2 and/or MUC2 were not independently associated with recurrence or prognosis. Conclusion: These models are simple and readily available, and distinguish the risk and prognosis in patients with CC stages I and II; these models require cheaper processes than the use of more sophisticated molecular biology techniques. They may guide either the need for adjuvant therapy versus post-operative surveillance only, as well as aid in the design of clinical trials.